Simulation Study of Dynamic Characteristics of Hot Pepper Harvester - 강석호; 김준희; 김영수; 하유신; 우승민 (Journal of Biosystems Engineering, 45(4), 2020)
Purpose Determining the safety conditions of a hot pepper harvester to mechanize harvesting. Methods The dynamic characteristics of a hot pepper harvester were analyzed with the dynamic simulation program RecurDyn. Results The pepper harvester can climb a maximal slope of 25° under full loading conditions; the maximal allowable height of an obstacle over which the harvester can drive is 450 mm; the minimal rotation radius during a spin turn is 870 mm. Conclusions Considering its dynamic characteristics, the harvester can be applied on over 95% of domestic upland fields. The safety accident rate can be decreased with the use of the spin turn method. In conclusion, the dynamic characteristics are sufficiently safe for the domestic upland fields. KCI Citation Count: 0